Virtual Colonoscopy and Abdominal Imaging. Computational Challenges and Clinical Opportunities Second International Workshop, Held in Conjunction with MICCAI 2010, Beijing, China, September 20, 2010, Revised Selected Papers - Yoshida, Hiroyuki; Cai, Wenli; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the International Workshop on Computational Challenges and Clinical Opportunities in Virtual Colonoscopy and Abdominal Imaging, held in conjunction with MICCAI 2010, in Beijing, China, on September 20, 2010. The 19 revised full papers presented were carefully reviewed and selected from 26 submissions. The papers are organized in topical sections on CT colonography CAD, abdominal imaging, and virtual colonoscopy.
Keywords: Computer science; Radiology, Medical; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; User Interfaces and Human Computer Interaction; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; Imaging / Radiology